(untitled) (Journal of Hama University, 2024)
Bran bread, prepared from a mixture of wheat flour and bran, is one of the most important functional foods and therefore there is a need to enhance its health benefits and nutritional value. The orange peels, that are resulting from the orange juice factories, are also considered a promising by-product in the field of food industry. So, the effect of using different ratios of orange peel powder (2.5, 5, 7.5, and 10)% on some physical and rheological properties of flour, as well as the sensory and chemical properties of bran bread was determined. The results of the flour mixtures study showed a significant decrease in wet gluten, falling number, and sedimentation number (P<0.05) with higher addition percentage. The results of the Mixolab apparatus showed an increase in the percentage of water absorption, but a decrease was observed in mixing properties, gluten quality, and starch gelatinization with addition in the increase of ratios. On the other hand, retrogradation characteristics improved when addition. It was observed that a higher percentage of moisture, ash, crude fiber, lipids, phenolic content, antioxidant capacity, and a significant decrease in the percentage of protein and carbohydrate were observed as addition ratios increased. The appearance of yellow color and the smell of oranges in bread was observed when adding orange peels, but it was pleasant at the low percentage of addition. Overall, the 2.5% addition rate gained acceptance when conducting the sensory evaluation.